2020
DOI: 10.1186/s12876-020-01478-7
|View full text |Cite
|
Sign up to set email alerts
|

Classification of gastrointestinal symptom patterns in young adults

Abstract: Background The purpose of this study was to identify common gastrointestinal (GI) symptom groups using the Patient-Reported Outcomes Measurement Information System - GI symptom scales (PROMIS-GI) within a large sample of young adults. An attempt was made to relate the emergent groups to the Rome IV disorders of gut-brain interaction symptom domains. The PROMIS-GI is a freely available, adaptable, normatively referenced symptom measurement system that is applicable to many health assessment situations. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 41 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Gastrointestinal events such as bloating, abdominal pains and constipation have been observed in the 'healthy control' groups in observational studies (Azpiroz et al, 2015;Del Piano et al, 2010;Laurikka et al, 2016) and in epidemiological studies with 'general populations' (Avramidou et al, 2018;Sezgin et al, 2019;Tielemans et al, 2013) implying that, for many, a degree of GI discomfort is considered normal. It has been found that even mild GI disturbances can be associated with anxiety/depression (Vivier et al, 2020) and impairments in quality-of-life (Tielemans et al, 2013) highlighting the necessity to better understand the GI characteristics of healthy populations and the potential impacts of probiotic supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal events such as bloating, abdominal pains and constipation have been observed in the 'healthy control' groups in observational studies (Azpiroz et al, 2015;Del Piano et al, 2010;Laurikka et al, 2016) and in epidemiological studies with 'general populations' (Avramidou et al, 2018;Sezgin et al, 2019;Tielemans et al, 2013) implying that, for many, a degree of GI discomfort is considered normal. It has been found that even mild GI disturbances can be associated with anxiety/depression (Vivier et al, 2020) and impairments in quality-of-life (Tielemans et al, 2013) highlighting the necessity to better understand the GI characteristics of healthy populations and the potential impacts of probiotic supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…GI diseases can be categorized as either functional, which are not accompanied by visible structural changes, or structural, such as inflammatory bowel disease (IBD), where both function and appearance of the GI tract are affected [ 2 ]. On the other hand, functional GI diseases are characterized by symptoms (including pain, constipation, nausea, bloating, and diarrhea) without any apparent structural changes to the GI tract [ 3 ]. GI diseases are among the most common reasons people seek medical care [ 4 ], and are typically caused by infections, unhealthy diet, stress, and medications’ side effects [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a growing number of studies suggest an increasing trend in the prevalence of functional gastrointestinal disorders in youths. Notably, as many as 65% of the youths are experiencing gastrointestinal symptoms, and almost one-third are seeking medical care (4). In addition, gastrointestinal symptoms are one of the most prominent somatic symptoms found in patients with mental disorders, including anxiety, depression, and autism spectrum disorder (5), which can negatively affect the youths on physical, mental, and social levels (6).…”
Section: Introductionmentioning
confidence: 99%